The Importance of Marketing Research in Small Business and Entrepreneurship - Eshanova Guzal Baratovna; Khurramov Ortikjon Kayumovich (Scientific Trends, 2024)
The article examines the importance of marketing research in small business and entrepreneurship in terms of marketing innovations. As well as key and fundamental issues related to innovations and their classifications, the role and place of marketing innovations, various classifications of marketing innovations are studied and a new approach based on the stages of the marketing management process is substantiated, the role of marketing innovations in small business and entrepreneurship is assessed.
Keywords: Small business, entrepreneurship, marketing innovation, marketing research, competitiveness.